A Study of Students' Experiences of Formative and Summative Assessment in Open Distance Learning: Insights from Meta-synthesis. (1st October 2016) - Mafenya, Patrick Nkhangweleni
Abstract: This paper reports on the analysis of students' experiences of formative and summative assessment inorder to articulate new insights relating to the most efficient and effective means of assessing students in distanceeducation contexts. Relatively little research appears to have been carried out to ascertain students' experiences andbeliefs regarding formative and summative assessments, and yet this is fundamental knowledge if one is serious aboutmaking changes in practice. This systematic document analysis purports to fill the gap in this area and confines itselfto students at the University of South Africa (Unisa), a dedicated distance education university. The paper qualitativelysurveyed the literature from 2005-2016. This paper was underpinned by the research question: What are students'experiences of formative and summative assessments in open distance learning? The analysis produced results thatcould be used to improve student learning and motivation.